The Found Play: Learning and Teaching the Value of Interpretive Reading and Writing - Randi Patterson; Kim Jernigan (Journal of the Assembly for Expanded Perspectives on Learning, 1995)
The "found" play is designed to make explicit the interpretive strategies that students use in everyday life, in a literary work, and in critical reading and writing.